1987
DOI: 10.1111/j.1365-2141.1987.tb02264.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of coagulation abnormalities following Russell's viper bite in Burma

Abstract: The evolution of coagulation abnormalities was studied in Russell's viper bite victims who, on admission to hospital, showed no clinical signs of systemic envenoming. Based on the laboratory results and subsequent clinical course, three groups were distinguished. The first group, consisting of five cases, showed no activation of coagulation at any stage. The second group, consisting of six cases, developed mild to moderate abnormalities in some tests, particularly in the aPTT and factor V assay, which correcte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Russell's viper venom contains factor X and factor V activators which result in the activation of the clotting pathway manifesting as venom induced consumption coagulopathy (VICC) [18] , [19] . VICC in Russell's viper envenoming is characterised by a prolonged prothrombin time (PT) or international normalised ratio (INR), decreased levels of fibrinogen, decreased levels of factor V, decreased levels of factor X, and elevated d-Dimer concentrations [6] , [20] [22] . Once antivenom is administered there is a resolution of VICC with normalising of the clotting function times and replenishing of the clotting factors including a gradual increase in fibrinogen levels.…”
Section: Introductionmentioning
confidence: 99%
“…Russell's viper venom contains factor X and factor V activators which result in the activation of the clotting pathway manifesting as venom induced consumption coagulopathy (VICC) [18] , [19] . VICC in Russell's viper envenoming is characterised by a prolonged prothrombin time (PT) or international normalised ratio (INR), decreased levels of fibrinogen, decreased levels of factor V, decreased levels of factor X, and elevated d-Dimer concentrations [6] , [20] [22] . Once antivenom is administered there is a resolution of VICC with normalising of the clotting function times and replenishing of the clotting factors including a gradual increase in fibrinogen levels.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study by Than et al found a similar association between venom concentrations and the severity of the coagulopathy. [ 15 ] There was an association between venom concentrations and factor V and Factor X, consistent with the Factor V activator and Factor X activator toxins in the venom.…”
Section: Discussionmentioning
confidence: 54%
“…[ 14 – 17 ] Two studies also reported serial measurements of factor V and factor X, with initial low levels that recovered over 24 hours consistent with our study. [ 15 , 16 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search found numerous clinical studies from a range of different settings that have used a WBCT, including from Australia [ 30 ], India [ 31 ], Sri Lanka [ 32 ], Thailand [ 33 , 34 ], Myanmar [ 35 , 36 , 37 , 38 ], Nigeria [ 25 ], Brazil [ 39 ] and Papua New Guinea [ 40 , 41 ]. Further, the WBCT has been used to detect VICC caused by taxonomically diverse snakes, including true vipers such as Russell’s viper ( Daboia russelii ) [ 12 , 31 , 34 , 35 , 36 , 37 , 38 , 42 , 43 , 44 , 45 ], saw-scaled viper ( Echis carinatus ) [ 32 ], pit-vipers such as Bothrops jararaca [ 39 , 46 ], South-Asian hump nosed pit vipers ( Hypnale hypnale , Hypnale zara , Hypnale nepa ) [ 14 , 28 , 47 ], Malayan pit viper ( Calloselasma rhodostoma ) [ 48 ] and green pit vipers ( Trimeresurus albolabris and Trimeresurus macrops ) [ 49 , 50 ], as well as Australasian elapids such as Western brown snake ( Pseudonaja nuchalis ) [ 30 ], mulga snake ( Pseudechis autralis ) [ 30 ], Papuan taipan ( Oxyuranus scutellatus canni ) [ 40 , 41 ], Papuan black snake ( Pseudechis papuanus ) [ 51 ], some colubrids such as Philodryas olfersii [ 52 ] and Philodryas patagoniensis , and lamprophiids such as Mock viper ( Tomodon dorsatus ) […”
Section: Types Of Bedside Coagulation Tests For Viccmentioning
confidence: 99%